DAMPAK KONSUMERISME BUDAYA KOREA (KPOP) DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI MALANG - Nisrina, Dzakkiyah; Widodo, Incka Aprillia; Larassari, Indah Bunga; Rahmaji, Fikri (Jurnal Penelitian Humaniora, 2020)
The rapid flow of globlalization makes foreign cultures enter through several media platforms supported by easy internet access. Including KPOP culture that entered and spread among teenagers, especially students. KPOP culture is often associated with consumerism because of the level of spending money on KPOP stuff on a regular basis in a certain period of time. The purpose of this study was to determine the impact of KPOP cultural phenomena on economic, social and cultural aspects. The method in this study was a qualitative method with a descriptive approach. The data collection technique was done by conducting observations and interviews. Data analysis techniques was conducted through several stages, namely: Data reduction, categorization/grouping, data process, data analysis. The results of this study indicated that Korean pop culture was so persuasive that it caused changes in people's lives which are unwittingly moved by the capitalists